Triple Immunotherapy Overcomes Immune Evasion by Tumor in a Melanoma Mouse Model - Jallad, Mary-Ann N.; Jurjus, Abdo R.; Rahal, Elias A.; Abdelnoor, Alexander M. (Frontiers in Oncology, 2020)
Background: Melanoma is a malignancy with increasing incidence that underlies most skin cancer-related deaths. Advanced melanoma patients still have poor prognosis despite recently developed immunotherapies. This study devises a triple immunotherapy to treat melanoma in a mouse model. The combination includes anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4) antibodies, Monophosphoryl-lipid-A (MPLA), and an Indolamine-Dioxygenase-1 (IDO1) inhibitor. The aim of the study is, first, to rule out any major toxic effects related to this therapy and, second, to assess its antitumor effects. Methods: Cancer-free C57BL/6 mice were randomized into control groups and groups receiving single, dual, or triple therapies of the defined treatments. Clinical signs, weight gain, and histological sections from their main organs were assessed. Then, melanoma-bearing mice were segregated into similar groups, monitored for survival, and their tumor size was measured repeatedly. Finally, flow cytometry was used to analyze immune cell populations in the tumor masses including CD4+, CD8+, and regulatory T cells in addition to natural killer cells. Results: No adverse effects were detected in any of the treated groups. Survival analysis indicated that the groups receiving dual or triple therapies had prolonged survival compared to the controls. However, the group receiving triple therapy was the only group to show statistically significant increase in survival compared to the controls. Tumor size progression paralleled the survival outcome. The group receiving the triple therapy showed statistically significant smaller tumor sizes compared to all the other groups throughout the whole monitoring period. Flow cytometry used to analyze immune cell populations in the tumor mass indicated that the triple immune therapy was capable of significantly enhancing the natural killer cell counts as well as the CD3+CD4+/Treg and CD3+CD8+/Treg ratios possibly enhancing the anti-tumorigenic environment. Conclusions: Generated data rule out any major adverse events pertaining to the triple immunotherapy and reveal its enhanced effectiveness in thwarting melanoma progression over all other tested treatments.